Suicidology Needs a More Inclusive Approach for Low and Middle‐Income Countries - S. M. Yasir Arafat; David Lester (Health Science Reports, 2025)
ABSTRACT Background and Aims Suicide is a global challenge. About three‐quarters of suicides happen in low‐ and middle‐income countries (LMICs). There are disparities in research and publication opportunities between countries based on income category. We aimed to discuss the disparities in research and publication on suicide between high‐income countries and LMICs. Methods We made a search in Scopus with the term “suicide” in early February 2025 and noted the number of publications and publishing journals. Results Along with suicidology journals, mental health journals are publishing research on suicide. There are no open access journals indexed in PubMed, Scopus, and PsycINFO which have no concerns about limited space. The leading three journals with good indexing follow a subscription/hybrid model with limited space that has results in the exclusion of papers of authors from LMICs. Conclusions Immediate attention is warranted to ensure that research on suicidal behavior from LMICs be solicited and published in journals currently available in the major indexing services. An open access journal focused on suicidal behavior without page limitations and with minimal or zero cost would be very useful.